Corporate governance and business innovation among listed Moroccan companies - Samlal, Zoubida (2020)
Purpose: This paper aims to clarify the relationship between corporate governance (GOV) and business innovation (INOV). Does it provide the empirical evidence of how different GOV mechanisms affect INOV within listed Moroccan companies? Design/methodology/approach: The paper opted for a confirmatory quantitative study using a closedended questionnaire using a fifth-degree Likert scale. The questionnaire was administered to 54 listed Moroccan firms represented by their senior management having mainly a finance and economics background. Findings: The paper provides empirical insights and evidence about how mechanisms of GOV impact INOV within listed Moroccan companies. It suggests that effective mechanisms of GOV foster and incubate INOV. Research limitations/implications: There have been very empirical studies that investigate the relationship between GOV and innovation. As such, the authors’ conceptual framework relies more on the theoretical aspect of this subject than empirical one. Therefore, researchers are encouraged to test the proposed propositions further. Originality/value: A review of the few existing empirical studies shows mitigated results regarding the relation between GOV and innovation. The findings of this study show a significant positive relation between GOV and its mechanisms and INOV. Doi: https://doi.org/10.1108/JEFAS-05-2019-0074